Internet of Things Technology and its Applications in Smart Grid - Liu Hua; Zhang Junguo; Lin Fantao (Institute of Advanced Engineering and Science, 2014)
Smart grid is the latest trend of development and reform in today’s world, and it is also a major technological innovation and development trend in the 21st century. Internet of Things technology is a new information processing and acquisition method, and it has been widely used in intelligent transportation, environmental monitoring and other fields. Internet of Things is an important technical mean to promote the development of smart grid. Using Internet of Things technology can effectively integrate the infrastructure resources in communications and electrical power system, increase the level of power system information, and improve the utilization efficiency of infrastructures in the existing power system. In this paper, the concept of smart grid and Internet of Things are briefed, thus the urgency of its applications in smart grid are pointed out. Meanwhile, a research and design in the construction of smart grid which is based on Internet of things are made, and the design and implementation in typical application links, including wind power prediction, condition monitoring of overhead transmission lines, power monitoring, smart home and asset management are elaborated emphatically. Finally, the problems in applications and future research direction are also analyzed. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4178